Implementasi Kurikulum Merdeka dalam Proses Pembelajaran “Pembelajaran Olah Tubuh” Anak Usia Dini di Kota Batu - I Bagus Endrawan; Hilmy Aliriad; Martinus (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
Effective learning is an important aspect for students as a provision for the introduction of field schooling (PLP) for students. The purpose of this study was to determine how much students can apply effective learning models in the learning process when following PLP, as well as how the application of these models affect the effectiveness of learning when following PLP. The design of research conducted in this study is qualitative research with descriptive approach. The population in this study as many as 55 students and then sampled a number of 30 students with random sampling. The results of the observation sheet showed that most students (70%) can apply effective learning models in the learning process when following PLP. While the other 30% still have difficulty in implementing the model. The results of data reduction from interview sheets showed that most students (80%) stated that the application of effective learning models in PLP makes learning more fun and effective. Another 20% stated that they had difficulties in implementing the model. The results of data reduction from the questionnaire showed that most students choose expository learning (20%) Problem-Based (60%) and cooperative learning (15%), most students can apply problem-based learning models in the learning process when attending PLP. This can be seen from the reduction of observation sheet data which shows that 70% of students can apply the model. The results of interviews and questionnaires also showed that most students stated that the application of effective learning models in PLP makes learning more fun and effective.